Law Sanctions Article 300 And 307 Law Number 22 Of 2009 Concerning Traffic Traffic and Road Transport (Llaj) Against Vehicle in Goods - Feriza, Gousta; Hadi, Lola; Arianto, Henry; Oktaviani, Desy (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to further analyze the imposition of ticket sanctions for motorists loaded with goods on the toll road. Four drivers of cargo vehicles that have received ticketing sanctions were interviewed to get more detailed and valid information regarding the ticketing sanctions. Furthermore, the information obtained from the four respondents will be analyzed in the form of qualitative analysis. In addition, information from the authorities will also be explored further in order to get a fair view of the two parties. From the research results obtained information about the process of applying two articles namely Article 300 and Article 307The Traffic and Road Transport Law (LLAJ), which is used by the authorities in providing ticketing sanctions for motorists loaded with goods. In addition, there are also other factors besides the Traffic and Road Transportation Law (LLAJ) which are used by the authorities in providing ticketing sanctions for motorists loaded with goods.